Construction parameters that affect the air leaks of the envelope in dwellings in Madrid - González-Lezcano, Roberto Alonso; Sanglier Contreras, Gastón; Iglesias Sanz, Carlos Miguel; Sancho Alambillaga, Rocío; López Fernández, Eduardo José (Frontiers in Built Environment, 2023)
In buildings, there is also ventilation, or rather, a lack of air tightness, which facilitates air leaks, from the outside to the inside, and vice versa, and which is not controlled. Cold air enters through the enclosure, and warm air loses to the outside, due to the poor hermeticity of the facades, roofs, carpentry, ducts, etc. In order to quantify the airtightness in multi-family dwellings in Madrid, 151 Blower Door Tests have been carried out in multi-family dwellings built in different periods whose execution has been regulated by the UNE-EN 13829 standard. Through its quantification by an n50 value, average values of 5.8 renovations per hour have been obtained; in addition to detecting the main points where air infiltration occurs. The constant improvement in the transmittance of the construction elements has meant that the entry of outside air has progressively taking on greater relevance in the total energy consumed by the residential sector. But the uncontrolled movement of air through the building envelope. It not only implies higher energy consumption, but also generates a series of problems that affect the health of its occupants: lack of thermal comfort, entry of pollutants and odors, noise, inadequate operation of ventilation systems, less protection against fire.,etc.